2015
DOI: 10.1177/0956797615591863
|View full text |Cite
|
Sign up to set email alerts
|

Creativity and Memory

Abstract: After receiving an episodic specificity induction - brief training in recollecting details of a recent event - people produce more episodic details when imagining future events and solving means-end problems than after receiving a control induction not focused on episodic retrieval. Here we show for the first time that an episodic specificity induction also enhances divergent creative thinking. In Experiment 1, participants exhibited a selective boost on a divergent thinking task that involves generating unusu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
110
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 209 publications
(126 citation statements)
references
References 31 publications
8
110
1
Order By: Relevance
“…The episodic specificity induction did not alter the overall relationship between internal and external details, meaning that if the generation of external details is entirely a secondary by-product of amount of internal details (or vice versa), a reciprocal effect between the two should be observed. However, it has previously been shown that in most experiments the episodic specificity induction increases internal details, but does not decrease external details (Madore et al, 2014; Madore, Jing, et al, 2016; Madore & Schacter, 2014, 2016; Madore, Szpunar, Addis, & Schacter, 2016; but see Jing, Madore, & Schacter, 2016; Madore, Addis, & Schacter, 2015). Furthermore, different types of future imaginations can alter the amount of internal details generated, with no concurrent effects on external details (de Vito, Neroni, Gamboz, Della Sala, & Brandimonte, 2015; see also Neroni, Gamboz, De Vito, & Brandimonte, 2016), and age-related decreases in internal details have been reported even when the number of external details does not differ with age (Madore & Schacter, 2014; Zavagnin et al, 2016).…”
Section: Discussionmentioning
confidence: 94%
“…The episodic specificity induction did not alter the overall relationship between internal and external details, meaning that if the generation of external details is entirely a secondary by-product of amount of internal details (or vice versa), a reciprocal effect between the two should be observed. However, it has previously been shown that in most experiments the episodic specificity induction increases internal details, but does not decrease external details (Madore et al, 2014; Madore, Jing, et al, 2016; Madore & Schacter, 2014, 2016; Madore, Szpunar, Addis, & Schacter, 2016; but see Jing, Madore, & Schacter, 2016; Madore, Addis, & Schacter, 2015). Furthermore, different types of future imaginations can alter the amount of internal details generated, with no concurrent effects on external details (de Vito, Neroni, Gamboz, Della Sala, & Brandimonte, 2015; see also Neroni, Gamboz, De Vito, & Brandimonte, 2016), and age-related decreases in internal details have been reported even when the number of external details does not differ with age (Madore & Schacter, 2014; Zavagnin et al, 2016).…”
Section: Discussionmentioning
confidence: 94%
“…As noted earlier, effects of the specificity induction have been documented on subsequent tasks that are thought to draw on episodic retrieval, including memory, future imagining, means-end problem solving, and divergent thinking tasks (Madore et al, 2014, 2015; Madore & Schacter, 2014, 2015). Equally important, the specificity induction has had no detectable impact on the performance of subsequent tasks that are thought to rely on primarily semantic retrieval or non-episodic narrative processing, such as describing a picture (Madore et al, 2014), generating word definitions (Madore & Schacter, 2015), or generating object associations and semantic solution words (Madore et al, 2015). Schacter and Madore (in press) have suggested that the CI-based induction biases a subsequent episodic retrieval orientation toward a focus on specific event details, such that individuals construct more detailed mental scenes or events after a specificity induction than a control induction.…”
mentioning
confidence: 81%
“…A total of 10 participants were excluded due to experimenter error (2 participants), incompletion of the experiment (5 participants), or noncompliance (3 participants), leaving 25 participants in the final sample. Before the study was run we performed a power analysis to determine that a sample size of at least 24 useable participants was necessary to observe a medium-sized effect of the induction (power > .80, α = .05, two-tailed, for a within-subjects design, d = 0.60), which has also been the case in prior induction studies (e.g., Madore et al, 2014, 2015). Given scheduling constraints with multiple sessions, data collection was stopped once it was determined that approximately enough useable participants had been run to reach this number.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from increasing the level of detail when recalling past and imagining future experiences (Madore et al, 2014), other known effects of the specificity induction on subsequent tasks include boosting the number of steps generated during problem solving (Jing et al, 2016; Madore & Schacter, 2014), increasing the number of creative solutions generated during divergent thinking tasks (Madore, Addis, & Schacter, 2015; Madore, Jing, & Schacter, 2016), and boosting the level of concreteness and detail during episodic reappraisal (Jing et al, 2016). Critically, whereas the specificity induction impacts performance on subsequent tasks that are thought to be dependent on episodic memory, it has no detectable impact on the performance of tasks that are thought to rely on primarily semantic retrieval or non-episodic narrative processing, such as describing a picture (Madore et al, 2014), generating word definitions (Madore & Schacter, 2015), or generating object associations and semantic solution words (Madore et al, 2015).…”
Section: Introductionmentioning
confidence: 99%